Financial Meltdown in the Mainline? - Mead, Loren B. (Rowman & Littlefield Publishers, 1998)
Intentionally provocative, Alban founder and former president Loren Mead’s dynamic work sets out dramatic and compelling challenges for today’s churches. Mead chose the word "meltdown"-a strong term, indeed-very carefully and consciously. His clarion call urges congregations to direct attention to their dwindling financial resources and their unreliable fiscal practices, and to take major action now-or face disaster in the future. Mead addresses changing church giving patterns; the inconsistent ways congregations keep financial records; the lack of coordinated short- and long-range planning; the need for knowledge of sound financial techniques such as accounting for inflation; an over-reliance on "restructuring" to fix problems; and lack of defensive planning for operational costs.